The foraging preferences of two species of Melissodes Latreille (Hymenoptera, Apidae, Eucerini) in farmed sunflower in Argentina - Cilla, Gabriela (2012)
The present study addresses the pollen preferences of two species of wild bees of the genus Melissodes in the intensively farmed temperate Pampean region of Argentina. The resources used by M. (Ecplectica) tintinnans and M. (Ecplectica) rufithorax were studied in a commercial plot of sunflower and its field margins in the locality of Carlos Casares, province of Buenos Aires. Surveys before, during and after the bloom of sunflower were carried out. The bees emerged synchronously with the beginning of the bloom, but continued foraging for over a month after maturation of the crop. Pollen analyses of scopal loads indicated that sunflower was a major component of the diet. Bees also collected pollen from other Asteraceae during and after the blooming of the sunflowers. Pollen from Ligustrum sp. and Eucalyptus sp., two trees common in the hedgerows, was also collected in significant amounts. The vegetation on the field margins facilitated maintenance of the populations after the blooming of the sunflower. The two species of native Melissodes used pollen of plant taxa that are frequent and widespread in the Pampean agricultural ecosystems. This fact, together with their habit of nesting in aggregations, indicates that these bees represent a valuable resource as crop pollinators.